Strategi Bimbingan dan Konseling dalam Mengatasi Rendahnya Kepercayaan Diri Siswa: Sebuah Kajian Literatur - Hijr Amelya; Risma Anita Puriani (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Self-confidence is an important psychological aspect that affects students' academic, social, and emotional success. Students with low self-confidence often struggle with interactions, expressing opinions, and optimizing their academic potential, which can negatively impact their personal development in school. Therefore, this issue requires attention through appropriate guidance and counseling services. This study aims to review various guidance and counseling strategies to address low self-confidence in students based on a literature review of the last six years. The method used is a library study with a traditional literature review approach, analyzing 15 national and international journal articles. The results indicate that low self-confidence is influenced by internal factors (such as negative self-concept and low self-efficacy) and external factors (such as bullying experiences and lack of social support). The impacts include decreased academic performance, social barriers, and negative emotions such as anxiety. Various guidance strategies, such as individual counseling, group counseling with sociodrama, and empathetic teacher communication, have proven effective in enhancing students' self-confidence. These findings suggest that low self-confidence is not a permanent condition but can be addressed through planned and ongoing guidance interventions. .